THE IMPACT OF DIFFERENT FIBEROPTIC INTUBATION TECHNIQUES ON HEMODYNAMIC STABILITY AND TRACHEAL TRAUMA IN LAPAROSCOPIC SURGERY: A PROSPECTIVE STUDY (European Journal of Interdisciplinary Research and Development, 2025)
Laparoscopic procedures involve pneumoperitoneum and the Trendelenburg position, complicating airway management. Various fiberoptic techniques (TOB) are used in difficult airway scenarios (DAW).